The Hurdles From Bench to Bedside in the Realization and Implementation of a Universal Influenza Vaccine - Valkenburg, Sophie A.; Leung, Nancy H. L.; Bull, Maireid B.; Yan, Li-meng; Li, Athena P. Y.; Poon, Leo L. M.; Cowling, Benjamin J. (Frontiers in Immunology, 2018)
Influenza viruses circulate worldwide causing annual epidemics that have a substantial impact on public health. This is despite vaccines being in use for over 70 years and currently being administered to around 500 million people each year. Improvements in vaccine design are needed to increase the strength, breadth and duration of immunity against diverse strains which circulate during regular epidemics, occasional pandemics, and from animal reservoirs. Universal vaccine strategies which target more conserved regions of the virus, such as the HA-stalk, or recruit other cellular responses, such as T cells and NK cells, have the potential to provide broader immunity. Many pre-pandemic vaccines in clinical development do not utilise new vaccine platforms but use ‘tried and true’ recombinant HA protein or inactivated virus strategies despite substantial leaps in fundamental research on universal vaccines. Significant hurdles exist for universal vaccine development from bench to bedside, so that promising pre-clinical data are not yet translating to human clinical trials. Few studies have assessed immune correlates derived from asymptomatic influenza virus infections, due to the scale of a study required to identity these cases. The realization and implementation of a universal influenza vaccine requires identification and standardised set points of immune correlates of protection, and consideration of dosage schedule to maximize vaccine uptake.